Hausaland A Nation in Nations: The Hausanization of Nigeria-Niger Republic Diplomatic Relations - Umate, Mohammed Dagozo; Idris, Aminu (Social Science Research, 2022)
The borderlines separating Niger Republic and Nigeria were artificially delineated by the European colonialists during the Berlin conference of 1884-85. Before the invention of the border, the Hausas in present-day Nigeria and the Niger Republic shared the same territory, lineage, religion, among others. However, the invention of border divided a group that was hitherto a single nation into two nations. However, despite the division, Hausa language remained an important diplomatic instrument that shapes and reshapes the diplomatic relations between Nigeria and the Niger Republic. The Hausanization of the diplomatic relations between the two countries emanates from thepre-colonial political institutions, cultural affinities and the domination of Nigeria’s political landscape by the Northern Nigerian political elites. Methodologically, this article relies on secondary and primary sources to collect data from diplomats, serving and retired military and para-military, civil servants among others. Thematic method using a descriptive coding system was adopted in the analysis of data generated from the in-depth interview. This study argues that Niger’s role during the Nigerian civil war, and the formation of the Nigeria Niger Joint Commission for Cooperation(NNJCC) were parts of the manifestation and institutionalization of Hausa as a major diplomatic instrument that governs the relations between Niger Republic and Nigeria. The major finding of the article reveals that, while the Northern Nigerians and Nigeriens perceived the Nigeria-Niger border as mere artificial lines that have no relevance, the Hausanization of diplomatic relations between the two countries has deepen the division between the Northern and Southern Nigeria.